2019
DOI: 10.14814/phy2.14303
|View full text |Cite
|
Sign up to set email alerts
|

The LRRC8 volume‐regulated anion channel inhibitor, DCPIB, inhibits mitochondrial respiration independently of the channel

Abstract: There has been a resurgence of interest in the volume-regulated anion channel (VRAC) since the recent cloning of the LRRC8A-E gene family that encodes VRAC.The channel is a heteromer comprised of LRRC8A and at least one other family member; disruption of LRRC8A expression abolishes VRAC activity. The best-inclass VRAC inhibitor, DCPIB, suffers from off-target activity toward several different channels and transporters. Considering that some anion channel inhibitors also suppress mitochondrial respiration, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The most potent, efficacious, and selective VRAC inhibitor identified to date is 4-(2-butyl-6,7-dichlor-2cyclopentylindan-1-on-5-yl) oxybutyric acid or DCPIB. However, even DCPIB has significant off-target activity toward the H-K-ATPase, inward rectifier and two-pore domain potassium channels, connexin hemichannels, glutamate transporters, and mitochondrial respiration (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…The most potent, efficacious, and selective VRAC inhibitor identified to date is 4-(2-butyl-6,7-dichlor-2cyclopentylindan-1-on-5-yl) oxybutyric acid or DCPIB. However, even DCPIB has significant off-target activity toward the H-K-ATPase, inward rectifier and two-pore domain potassium channels, connexin hemichannels, glutamate transporters, and mitochondrial respiration (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to consider that DCPIB might have significant off-target effects. A recent study demonstrated that DCPIB suppresses mitochondrial respiration independently of VSOR Cl − channel activity (Afzal et al, 2019). We suggest that the exposure to 10 µM DCPIB or Tamoxifen for several hours might similarly impair the viability of chondrocytes and promote cell death by exerting cytotoxic effects.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, SN-401 mediated rescue of islet insulin secretion under glucolipotoxic conditions in vitro also requires SWELL1. Finally, it is important to note that the studies demonstrating promiscuity of SN-401/ DCPIB with other ion channel targets all applied DCPIB at ~10-200 µM [68][69][70][71][72][73] . This is 100-200-fold higher than the concentrations required to potentiate SWELL1-dependent signaling in vitro (Figs.…”
Section: Discussionmentioning
confidence: 99%